Entre o Declínio Econômico e o Legado da Memória: A Preservação do Patrimônio Imaterial em Santo Antônio de Leverger/MT - Carignani, Gisele; Seabra, Jessica; Ravache, Rosana Lia; Reis, Amábile Alencar; Gonçalves, Ana Kédma; Antunes, Beatriz Linhares (Technical and Scientific Journal Green Cities, 2025)
Objective -To analyze the resilience of the intangible cultural heritage of Santo Antônio de Leverger/MT in the face of local economic decline, highlighting the historical predominance of the Cuiabá River and the importance of heritage education for the valorization of knowledge and memories. Methodology -The study employs a qualitative and bibliographic review approach, based on historical documents and key concepts of memory, culture, and heritage. The analysis integrates the historical context of the municipality’s formation with the identification of contemporary challenges to cultural preservation. Originality/Relevance -This work addresses a gap in studies that correlate the decline of historically strong economies with the permanence of cultural manifestations. Its academic relevance lies in the exploration of collective memory as an element of resistance and in the proposal of an educational methodology to safeguard the riverside identity. Results –The study finds that, despite the economic decline of the sugar mills, the riverside culture, based on orality and customs, has remained the main identity reference for the population. The article demonstrates that the valorization of intangible heritage is fundamental for the vital health of communities. Theoretical/Methodological Contributions –The study contributes theoretically by consolidating the relationship between collective memory and intangible heritage, and methodologically by proposing a didactic-pedagogical plan for cultural rescue and valorization, serving as a model for the conservation of intangible assets in scenarios of urban challenges. Social and Environmental Contributions - Socially, the article highlights the importance of strengthening the sense of belonging and local identity. Environmentally, it emphasizes the importance of the Cuiabá River as a historical and cultural protagonist, reinforcing the need for its preservation.